KEDUDUKAN DAN HAK BANK TERHADAP HAK PREFEREN UPAH BURUH DALAM KEPAILITAN - I Wayan Sukatra (University of Udayana, 2017)
The Bank is the creditor holder of the right of security of material in the form of mortgage right, categorized as separatist creditor. Insurers' rights to land and other property related to the land, namely the right of Dependent, are the security rights imposed on the Land Rights referred to in UU no. 5 of 1960 on the UUPA. This separatist position can execute its right as if there was no bankruptcy